Johnson's New Brunswick, Nova Scotia, Newfoundland and Prince Edward Id. - Johnson and Ward (Johnson and Ward, 1866)
Map late nineteenth century New Brunswick, Nova Scotia, Newfoundland, and Prince Edward Island railroads, cities, political divisions within each province. Relief shown by hachures. Scale [1:3,240,000].